Estudos genéticos sobre a virulência de Escherichia coli enteroagregativa atípica - Zamboni, Andresa [UNIFESP] (2006)
Escherichia coli enteroaggregative (EAEC) is emerging as a significant diarrheal pathogen. EAEC is defined by its characteristic “stacked brick” aggregative adherence (AA) pattern of adherence to HEp-2 cells. Most EAEC strains harbor a 60 to 65-MDa virulence plasmid (pAA). A 1-Kb fragment of pAA, referred to as the AA probe or CVD432, has been widely used for epidemiological studies. The pAA also encodes AA fimbrae (AAF) I, II, and III; the transcriptional activator AggR; enteroaggregative heatstable enterotoxin 1 (EAST1); a 104-KDa cytotoxin designated Pet; the cryptic secreted protein Shf; and a novel antiaggregation protein (dispersin) encoded by the aap gene. In addition to the pAA plasmid, some EAEC strains express putative virulence factors that are encoded on the chromosome, including a 116-KDa secreted mucinase (Pic), yersiniabactin (Irp2), and the E. coli a-hemolysin (a-Hly). Shigella enterotoxin 1 (ShET1) is encoded by the antisense strand of the pic gene. Few studies have evaluated the prevalence of EAEC markers in probe-negative strains, reported by us as atypical EAEC. By using atypical EAEC strains isolated in a case-control study, we assessed the prevalence of putative virulence factors, such as AAF/I, AAF/II, AAF/III, AggR, Aap, EAST-1, Pet, Shf, ShET1/Pic, Irp2, and a-Hly, in an attempt to identify their roles as enteric virulence factors. The majority of strains carried two or more of the genes, with two being the modal value; but two strains isolated from a control did not test positive for any of the factors. The AAF, aggR, and aap genes were present in only a minority of strains. The astA, pet, shf, ShET1/pic, irp2 and hly genes were found more frequently in the patients than in the controls. The combination astA and shf was found in 16 strains (57%), followed by 7 strains (25%) possessing the combination astA, shf, and irp2. The common virulence markers found in strains included the Pet, EAST1, Shf, Irp2, ShET1/Pic, and Hly virulence markers. EAST1 and Shf were the most frequently detected markers (61%) in strains and were found to be significantly associated with diarrhea (P = 0,003 and P = 0,020, respectively). The majority (75%) of the EAEC isolates reacted with one of the antisera used. It was interesting that the strains belonging to serogroups O42, O126 and O162 were detected only in children with diarrhea.Plasmid analysis of 12 strains isolated from diarrhea showed that the majority of strains contained large plasmids. Two strains, one carrying only one plasmid (MA691-2) and another one any plasmid (RN153-1), were chosen for genetic studies on the identification of genes responsible for the AA phenotype. Plasmid from MA691-2 strain was transferred to E. coli K12 and no transformant or transconjugant harboring the plasmid or isogenic derivative strain lacking the plasmid was identified. A genomic cosmid library of EAEC RN153-1 was generated in E. coli K12, and the resulting clones were screened for aggregative adherence to HEp-2 cells. One cosmid clone, pVIII-F-1, exhibited the same adherence as the wild-type, albeit to a lesser extent. Transposon mutagenesis was utilized to identify the region of cosmid pVIII-F-1 responsible for the aggregative phenotype. Plasmid pBSL181 carrying mini-Tn10